Copper deposition in Wilson’s disease causes male fertility decline by impairing reproductive hormone release through inducing apoptosis and inhibiting ERK signal in hypothalamic-pituitary of mice - Wang, Tingting; Wu, Limin; Chen, Qiuying; Chen, Kuiyu; Tan, Fang; Liu, Jiabo; Liu, Xiang; Han, Hui (Frontiers in Endocrinology, 2022)
Wilson’s disease (WD) is an autosomal recessive disorder of copper metabolism characterized by liver and central nervous system dysfunction. Considerable evidence suggests that infertility is also very common in male patients with WD, but the exact molecular mechanisms involved remain unknown. In order to further investigate the pathological changes in the hypothalamic-pituitary-testicular (HPT) axis and its mechanisms, mice were divided into the normal control group (NC), WD model TX mice group (WD), dimercaptosuccinic acid–treated TX mice group (DMSA), and pregnant horse serum gonadotropin–treated TX mice group (PMSG). The copper content and morphology of hypothalamus and pituitary tissues, the ultrastructure and apoptosis of hypothalamus neurons and pituitary gonadotropin cells, the serum levels of reproductive hormones, and the pregnancy rate and litter size of the female mice were studied. The expression of apoptosis-related proteins and the phosphorylation of extracellular regulatory protein kinase (ERK) 1/2 in the hypothalamus and pituitary were detected. The results showed that the copper content was significantly increased in the WD group, and the histopathological morphology and ultrastructure of the hypothalamus and pituitary were damaged. The levels of the gonadotropin-releasing hormone, the follicle-stimulating hormone, the luteinizing hormone, and testosterone were significantly decreased. The apoptosis rate in the hypothalamus and pituitary was significantly increased. The expressions of proapoptotic proteins Bax and Caspase-3 were significantly increased, the expression of the anti-apoptotic protein Bcl-2 was significantly decreased, and the phosphorylation level of ERK1/2 was significantly decreased. Fertility is significantly reduced. After DMSA intervention, the hypothalamus tissue copper content decreased, the hypothalamus and pituitary tissue morphology and ultrastructure were improved, cell apoptosis was alleviated, the expression of Bax and Caspase-3 was significantly decreased, the expression of Bcl-2 was significantly increased, and the reproductive hormone level, phosphorylation level, and fertility were increased. Fertility was preserved after treatment with PMSG in male TX mice. These results suggest that copper deposition in WD causes male fertility decline by impairing reproductive neuroendocrine hormone release through inducing apoptosis and inhibiting the ERK signal in the hypothalamic–pituitary region. This study can also provide reference for the damage of copper pollution to the male reproductive system.